Synthesis of Hard Carbon from Waste Teak Wood Powder as Anode Material for Lithium-ion Batteries - Alfi Nur Aini; Dewi Ratnasari; Aninda Artatriska Meilana; Hendri Widiyandari (Journal of Physics: Theories and Applications, 2021)
Electrochemical energy storage technologies such as rechargeable batteries show considerable progress due to their high efficiency, flexible power, long life cycle, and low maintenance. Graphite is a common anode material used in lithium-ion batteries. However, there are several shortcomings in graphite anode material, one of which is poor structural stability. Therefore, hard carbon is the most promising candidate for lithium-ion battery anodes due to its high storage capacity, low working potential, and cycle stability. This research utilizes teak sawdust waste as a hard carbon battery anode. They were approached by the carbonization method at temperatures of 350°C and 450°C. In general, X-Ray Diffraction (XRD) results show an amorphous structure of carbon atoms. The morphological structure known through the Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) test shows a fiber shape. The mass percent of carbon at a temperature of 450°C was higher than at a temperature of 350°C, which was 67.93%. Then the battery performance test was carried out with the highest discharge capacity value obtained at a temperature of 450°C at 191.56 mAh/g. Based on the results of this study, teak sawdust waste material has the potential as an anode for rechargeable batteries and can prevent environmental pollution.